Political climate and regional well-being in Turkey - DENİZ, PINAR (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Politicians can use social and economic policies on clientelist grounds neglecting the efficiency and equity concerns of public policy. While incumbents might reward and punish voters based on party-specific fundamentals, the role of political ideologies and fragmentation is mostly neglected. For societies such as Turkey, where the ideological stance is mixed and the level of fragmentation is varying, the regional political climate has implications for regional well-being beyond the borders of political parties. Our findings for the post-2000s validate that regions that are ideologically closer to the right and the incumbent party (Justice and Development Party - AKP) attain higher well-being, while the opposite is true for ideologically polarized regions and regions closer to left-wing ideologies. The results are robust to the endogeneity of political climate and various model specifications.
Keywords: ideology; inequality; political climate; regional well-being; Turkey